Alpha-2-Macroglobulin Not Significantly Better Than Regular PRP For Knee Arthritis Symptoms. Issue 7 (31st July 2020) - Klein, David; Bloom, David; Campbell, Kirk; Gonzalez-Lomas, Guillem; Alaia, Michael; Strauss, Eric; Jazrawi, Laith; Thompson, Kamali
Objectives: Osteoarthritis, a degenerative and debilitating joint disease, is one of the most prevalent diseases in the United States. Despite the significant burden osteoarthritis can place on an individual and society, nonoperative treatment options are still very limited. Little clinical data exists on the use of injectable macromolecules for the treatment of osteoarthritis of the knee. Alpha-2-macroglobulin (A2M), a naturally occurring macromolecule, inhibits the many endogenous and exogenous proteinases presenting in the pathogenesis of osteoarthritis. To date, no studies exist evaluating the effectiveness of A2M with other intra-articular injectables. The purpose of this study is to compare the clinical effectiveness of intra-articular injection of A2M against both platelet-rich plasma (PRP) and corticosteroids. Methods: This prospective randomized control trial was conducted at a single medical center. Seventy-five patients with symptomatic knee osteoarthritis with Kellgren-Lawrence grade 2 or 3 were randomized into one of three cohorts receiving intra-articular injection. One group was given PRP, one group was given A2M, and one group was given corticosteroids. All groups had blood drawn to simulate A2M preparation. Patient reported outcomes were collected prior to injection, 6 weeks and 12 weeks following injection. Several measures were used for clinical assessment including the visual analog scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS), Lysholm, and Tegner scores. Results: Seventy-five patients with a mean age of 61.08 (± 8.48) were enrolled between June 2018 and February 2019. At six weeks, the A2M group had the greatest decrease in VAS (-1.60) and WOMAC (-10.9), however, the differences were not statistically significant. Between the injection and the twelve week visit, the A2M group had a statistically significant difference in WOMAC score compared with PRP (-18.43 vs -5.70, p <0.02). Overall, both corticosteroid (-1.57) and A2M (-1.70) had a similar improvement in VAS when compared with PRP (-0.61). These differences were also not statistically significant. Conclusions: Our study demonstrates Alpha 2 Macroglobulin shows similar effectiveness to corticosteroids in the treatment of knee osteoarthritis. Both A2M and corticosteroids appear to show marginally better effectiveness than PRP injection, however the differences are small and did not reach statistical significance in most outcome measures.